KOMUNIKASI LINGKUNGAN DALAM MENGEMBANGKAN KELESTARIAN HUTAN - Ch. Herutomo; S. Bekti Istiyanto (Universitas Prof. Dr. Moestopo (Beragama), 2021)
Forest sustainability will be maintained if there is sustainability of the ecological and economic functions of the forest, the ecological function is the fulfillment of forest resources as the carrying capacity of the environment and the economic function of the forest can improve the welfare of the community If the forest is damaged then these two functions will not be fulfilled. This is where community participation-based environmental communication is needed. The purpose of this study is to describe forest functions that require community participation which are grown through conceptual-based environmental communication. This study uses qualitative descriptive method. The result of this research is that sustainable forest development through the approach of welfare and community participation as a social forest concept can be positively correlated with the sustainability of the ecological and economic functions of forest resources, so that the community has a high sense of belonging to the forest which is positively correlated with the importance of maintaining forest sustainability. The need for forest conservation requires good environmental communication that can foster public awareness and participation in institutionally sustainable forest management such as the Community Forest Management Communication Forum (FK PHBM).